ICU nurses' perception of visits to patients - Dobrinić, Ines; Režić, Slađana (2020)
Introduction. Visits to patients are part of a positive and effective strategy of helping patients and their families to better adapt to the stress caused by a patient’s admission to an intensive care unit (ICU). Aim. To determine the ICU nurses’ perception of visits to patients. Methods. The study was conducted at the University Hospital Centre Zagreb (UHC). The cross-sectional study included nurses who work in ICUs. An anonymous, self-designed questionnaire was used and filled in by 44 respondents. The questionnaire consisted of 17 closed-ended questions pertaining to demographic data, questions related to information on visits and questions about the concept of open visits. Results. Out of the total number of 44 respondents, 25 respondents stated that their ICU has booklets about the manner of visits and visiting hours, and that they hand them out to families, while 19 respondents stated that they do not have such booklets. 61% of the respondents feel they have sufficient training to communicate with the patient’s family. 41% of the respondents said that the visits had a positive effect on the patient’s condition and only 2% stated that the visits had no positive effect. 57 % of the respondents think that visits sometimes have a positive effect on the patient’s condition. Of the total number of respondents, 84% feel that visiting hours should be limited. Respondents feel that visits sometimes impede them in their work (66%), while 59% of the respondents feel that visits help spread infections. Out of the total number of respondents, only 32% of them stated that they were familiar with the open ICU concept. Conclusion. More than half of the respondents stated that they have a written visiting policy on ICU wards, and that they are trained to communicate with the family members of patients. Most respondents feel that visits contribute to the spread of infections and that they would limit children’s visits to the ICU.
Uvod. Posjeti bolesnicima dio su pozitivne i učinkovite strategije koja pomaže bolesnicima i njihovim obiteljima da se bolje prilagode stresu koji nastaje prilikom prijama na odjel intenzivnog liječenja. Cilj. Cilj je rada utvrditi percepciju medicinskih sestara na odjelima intenzivne skrbi o posjetima bolesnicima. Metode. Istraživanje je provedeno u KBC-u Zagreb. Presječno istraživanje uključivalo je medicinske sestre koje rade na odjelima intenzivne skrbi. Primijenjena je anonimna anketa kreirana za ovo istraživanje, koju je ispunilo četrdeset i četiri ispitanika. Anketa se sastojala od 17 pitanja zatvorenog tipa koja su se odnosila na demografske podatke, pitanja povezana s informacijama o posjetima te pitanja o konceptu otvorenih posjeta. Rezultati. Od ukupnog broja od 44 ispitanika, 25 ispitanika navodi da postoje brošure o načinu i vremenu posjeta koje daju obitelji, dok 19 ispitanika navodi kako kod njih ne postoje takve brošure. Dovoljnu edukaciju za komunikaciju s obitelji bolesnika navodi da ima 61 % ispitanika. Da posjeti imaju pozitivan učinak na stanje bolesnika odgovorilo je 41 % ispitanika, a samo 2 % ispitanika smatra da posjeti nemaju pozitivan učinak. 57 % ispitanika smatra da posjeti ponekad imaju pozitivan učinak na stanje bolesnika. Od ukupnog broja ispitanika čak ih 84 % smatra da bi vrijeme posjeta trebalo biti ograničeno. Ispitanici smatraju da posjeti ponekad ometaju njihov rad (66 %), a 59 % ispitanika smatra da posjeti pridonose širenju infekcija. Od ukupnog broja ispitanika samo 32 % navodi kako im je poznat koncept otvorenog JIL-a. Zaključak. Više od pola ispitanika navodi kako imaju pisanu politiku posjeta na odjelima jedinice za intenzivno liječenje te da su educirani za komunikaciju s članovima obitelji bolesnika. Većina ispitanika smatra kako posjeti pridonose širenju infekcija te bi ograničili posjete djece u JIL-u.
Bibliografija: 19 jed.
Abstract ; Sažetak.
Keywords: Medicinske sestre -- Intenzivna skrb -- Posjeti bolesnicima